Ways to Develop the Creative Qualities of Technological Education Teacher - Chorshanbiyevich, Dusyarov Xudoymurod (Universitas Muhammadiyah Sidoarjo, 2022)
This article analyzes ways to develop the creative qualities of technological education teacher and emphazises the development of world civilization. Therefore, there are the concepts of